Quantized Grain Boundary States Promote Nanoparticle Alignment During Imperfect Oriented Attachment - Lange, Andrew P.; Samanta, Amit; Olson, Tammy Y.; Elhadj, Selim (Small (Weinheim an der Bergstrasse, Germany), 2020)
Oriented attachment (OA) has become a well‐recognized mechanism for the growth of metal, ceramic, and biomineral crystals. While many computational and experimental studies of OA have shown that particles can attach with some misorientation then rotate to remove adjoining grain boundaries, the underlying atomistic pathways for this “imperfect OA” process remain the subject of debate. In this study, molecular dynamics and in situ transmission electron microscopy (TEM) are used to probe the crystallographic evolution of up to 30 gold nanoparticles during aggregation. It is found that Imperfect OA occurs because 1) grain boundaries become quantized when their size is comparable to the separation between constituent dislocations and 2) kinetic barriers associated with the glide of grain boundary dislocations are small. In support of these findings, TEM experiments show the formation of a single crystal aggregate after annealing nine initially misoriented, agglomerated particles with evidence of dislocation activity and twin formation during particle/grain alignment. These observations motivate future work on assembled nanocrystals with tailored defects and call for a revision of Read–Shockley models for grain boundary energies in nanocrystalline materials. This study offers new insights into the crystallographic alignment of nanoparticles during self‐assembly and aggregation. The salient details reveal that grain boundaries between small particles (0–10 nm) rapidly “disintegrate” via deformation processes due to the quantization of grain boundary energies at these length scales.